Measuring the precise area of peripheral retinal non-perfusion using ultra-widefield imaging and its correlation with the ischaemic index. Issue 2 (1st July 2015) - Tan, Colin S; Chew, Milton C; van Hemert, Jano; Singer, Michael A; Bell, Darren; Sadda, SriniVas R
Abstract : Objective: To determine the calculated, anatomically correct, area of retinal non-perfusion and total area of visible retina on ultra-widefield fluorescein angiography (UWF FA) in retinal vein occlusion (RVO) and to compare the corrected measures of non-perfusion with the ischaemic index. Methods: Uncorrected UWF FA images from 32 patients with RVO were graded manually for capillary non-perfusion, which was calculated as a percentage of the total visible retina (uncorrected ischaemic index). The annotated images were converted using novel stereographic projection software to calculate precise areas of non-perfusion in mm 2, which was compared as a percentage of the total area of visible retina ('corrected non-perfusion percentage') with the ischaemic index. Results: The precise areas of peripheral non-perfusion ranged from 0 mm 2 to 365.4 mm 2 (mean 95.1 mm 2 ), while the mean total visible retinal area was 697.0 mm 2 . The mean corrected non-perfusion percentage was similar to the uncorrected ischaemic index (13.5% vs 14.8%, p=0.239). The corrected non-perfusion percentage correlated with uncorrected ischaemic index (R=0.978, p<0.001), but the difference in non-perfusion percentage between corrected and uncorrected metrics was as high as 14.8%. Conclusions: Using stereographic projection software, lesion areas on UWF images can be calculated in anatomically correct physical units (mm 2 ). Eyes with RVO show large areas of peripheral retinal non-perfusion.